Original paperSTYLE OF THINKING ABOUT DOPING AMONG SPORTSPERSONS: CHARACTERIZING THE ATTITUDES OF RISK-TAKERS AND RISK-AVOIDERS - Mroczkowska, H. (Biology of Sport, 2012)
The aim of the study is to describe the style of thinking about doping among risk-takers and risk-avoiders in three hypothetical situations varying according to the level of objective probability of an anti-doping test. A group of competitive athletes was assessed (N=23; modern pentathlon), mean age ~16.7 years, mean experience in sport 8 years. As the criterion for categorisation of athletes into risk-takers (N-6) and risk-avoiders (N-9), the scope of personally accepted risk in a situation of very high probability of an anti-doping test was assumed. An experimental technique developed for the use of these studies was applied to measure: 1) individual hierarchy of values possible to be lost as a consequence of using doping; 2) personally accepted level of risk of losing values in the three experimental situations: a) low objective risk (2 to 10), b) medium objective risk (5 to 10), c) high objective risk (8 to 10). In the attitude of the risk-avoiders the reluctance to risk the loss of each studied value grows together with the increase of the objective danger until the critical moment that they do not exceed (null risk tolerance). In the style of thinking of the risk-avoiders about doping, a logical translation occurs between what they value most and what they protect most. In the attitude of the risk-takers there is no such translation, and moreover, together with the increase of the objective danger of losing the valued goods, the readiness to sacrifice them as the result of the risky decisions does not weaken. The true character of a risk-taker and the personal need to take risks is revealed most strongly under circumstances of a high probability of losing the mostly highly valued goods. The risk-avoiders value their emotional health significantly more highly than do the risk-takers, while for the risk-takers winning medals is valued significantly more highly.